Schooling for tomorrow's America - Kysilka, Marcella L.; Davis, O. L. 1928- (Research in curriculum and instruction., 2014)
This book can be read by educators at all stages in their careers. What a great selection for a book study group of practicing teachers or for a seminar with graduate students. The authors share their thoughts about education for the future, but also inform us about the past. Whether you encounter this book as a textbook or for a professional learning community, the contents will inform and inspire you, encouraging you to think deeply and work towards the improvement of education.